1997
DOI: 10.3109/00016349709024366
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein in uncomplicated parturients delivered by Cesarean section

Abstract: The wide range of serum C-reactive protein concentrations during puerperium complicates its use as a simple marker in obstetric postoperative complications. However, after normal uncomplicated operative delivery, C-reactive protein concentrations rapidly decrease towards the baseline after the second to third postoperative day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 13 publications
(3 reference statements)
0
11
1
Order By: Relevance
“…Most frequently altered analytical values found in our cohort, with the exception of absolute lymphopenia, which has been described in COVID-19, 21,24,25 could be explained by most tests being conducted in the immediate postpartum, thus modifying neutrophil count, 26 fibrinogen levels, 26,27 D-Dimer levels, 26,28 and CRP concentration. 27,29 Regarding maternal prognosis, one patient (3%) succumbed to the illness. Although the patient was young, presence of obesity is a risk factor for mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Most frequently altered analytical values found in our cohort, with the exception of absolute lymphopenia, which has been described in COVID-19, 21,24,25 could be explained by most tests being conducted in the immediate postpartum, thus modifying neutrophil count, 26 fibrinogen levels, 26,27 D-Dimer levels, 26,28 and CRP concentration. 27,29 Regarding maternal prognosis, one patient (3%) succumbed to the illness. Although the patient was young, presence of obesity is a risk factor for mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have been conducted measuring this analyte during pregnancy with the use of different detection techniques and cut-off values. Some authors have reported an increase in concentration of CRP with labor, delivery and the immediate postpartum period; although the variability of the values used as abnormal makes generalization difficult 24, 25 . Various authors have attempted to associate serum concentrations of this acute phase reactant with adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…During expectant management, serum CRP levels of all mothers were similar, between 0.1 up to 10 mg/l. Serum CRP levels of all mothers rapidly rose immediately after vaginal delivery or Caesarean section up to 20 mg/l [16][17][18] and, thus, masked the reaction to infection.…”
Section: Pmn Blood Counts and Crpmentioning
confidence: 99%